2020
DOI: 10.1111/ejn.14932
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal study of the effects of tDCS on dorsolateral prefrontal and temporo‐parietal areas during dichotic listening

Abstract: The underlying neural mechanisms of transcranial direct current stimulation (tDCS), especially beyond the primary motor cortex, remain unclear. Several studies examined tDCS effects on either functional activity, neurotransmitters or behavior but few investigated those aspects together to reveal how the brain responds to tDCS. The objective is to elucidate the underlying mechanisms of tDCS using a multimodal approach that extends from behavioral to neurotransmitter levels of explanation. Thirty‐two healthy par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…A possible explanation for these inconsistent results may be provided by another study from our group [ 25 ], published after we had completed data collection for the present study, which found (a) no excitatory/inhibitory effect underneath the electrodes in the STG/DLPFC region with the ipsilateral frontotemporal montage and (b) that the electrical field was strongest in the left central sulcus region/Broca’s area—between the two electrodes. Thus, the modulation of internal source monitoring effects observed in the present study might result from an indirect stimulation of Broca’s area.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A possible explanation for these inconsistent results may be provided by another study from our group [ 25 ], published after we had completed data collection for the present study, which found (a) no excitatory/inhibitory effect underneath the electrodes in the STG/DLPFC region with the ipsilateral frontotemporal montage and (b) that the electrical field was strongest in the left central sulcus region/Broca’s area—between the two electrodes. Thus, the modulation of internal source monitoring effects observed in the present study might result from an indirect stimulation of Broca’s area.…”
Section: Discussionmentioning
confidence: 68%
“…The results in the offline experiment could have been confounded by the participants being tired after the scanning protocol or potentially less motivated to perform the source monitoring task. Secondly, participants in the offline experiment were performing an acoustic language task [i.e., dichotic listening, [ 16 ] in the MR scanner while receiving tDCS [ 25 ], which might have led to a different outcome as compared to the online experiment. Thirdly, there was a break of roughly 20 minutes between the termination of tDCS and the end of the source monitoring task, in which two more MR-sequences were applied and electrodes had to be removed from the scalp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both areas were scanned twice, once with a standard “Point RESolved Spectroscopy” (PRESS) sequence and once with a GABA-edited MEshcher-GArwood PRESS (MEGAPRESS) sequence, resulting in four spectra. Data processing followed a well-established pipeline in our group [ 24 , 36 ]. PRESS data were acquired at TE = 35 ms, TR = 1500 ms, 128 repetitions plus eight water-unsuppressed reference scans acquired automatically after the metabolite scans, with 4096 samples at sampling frequency 5 kHz.…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…By placing the typically excitatory anode over the hypoactive DLPFC area and the typically inhibitory cathode over the hyperactive TPC, it is assumed that the hypofrontality and hypertemporality is reversed and AVH frequency and severity reduced [ 1 ]. However, it is not certain whether this theory (henceforth termed “hypofrontal/hypertemporal reversal theory”) holds: Recent simulation/modelling studies have demonstrated that the peak of the electric field with a unihemispheric DLPFC/TPC montage lies between the two electrodes, in Broca’s area, rather than in DLPFC and TPC areas themselves [ 23 , 24 ]. Moreover, the assumption that the anode and cathode are generally excitatory and inhibitory, respectively, is no longer tenable [ 25 ].…”
Section: Introductionmentioning
confidence: 99%